PENENTU BELANJA MODAL DAN KONSEKUENSINYA PADA PENDAPATAN PERKAPITA STUDI PADA KABUPATEN/KOTA DI JAWA TENGAH TAHUN 2008-2010 (Students' Journal of Economic and Management, 2013)
This study aimed to determine the effect of fund balance consists of the General Allocation Fund, Special Allocation Fund, Financial Assistance from the Provincial Government and the Revenue and Capital Expenditure Allocation to determine the effect of capital expenditures in each district / city in the administrative area of Central Java Provincial Government the per capita income in the region. The data used in this study were obtained from various data sources such as data from the district budget / City, Allocation Funds Transfer from the Directorate General of Fiscal Balance regional Ministry of Finance of the Republic of Indonesia, Central Bureau of Statistics and Central Java to the research data period of 3 (three) years the Fiscal Year 2008-2010.The results are from four sources of funding DAU, DAK, Financial Aid and Provincial Government Revenue is the verdict that the district / city heavily dependent on government transfers funds on it with the greatest number of general allocation funds. Hypothesis test results showed the four fund balance of the General Allocation Fund and the Financial Assistance that significantly affect the allocation of capital expenditures in the district / town in the administrative region of Central Java province, while for components DAK, and Revenue does not significantly affect the allocation of Capital Expenditure . In this study, capital expenditure budget contained in the district / city government administrative region showed a positive effect on per capita income of the area. Keywords: Balance Fund, Capital Expenditure, Per Capita Income, Regency / City in Central Java